Growing towards disparity: geometric morphometrics reveals sexual and allometric differences in Aparasphenodon brunoi (Anura: Hylidae: Lophyohylinae) head shape - Fonseca, Roberta A. M. (2020)
Sexual dimorphism and allometry feature is the main categories of intraspecific variation found in the animal kingdom, and techniques such as Geometric Morphometrics are effective to investigate variations in shape. Considering that many vertebrates exhibit substantial allometry and sexual dimorphism, we test the hypotheses that (1) Aparasphenodon brunoi displays ontogenetic and static allometry; and that (2) there is sexual dimorphism in head shape in this species. We analyzed 75 specimens of A. brunoi from Parque Nacional da Restinga de Jurubatiba and found significant ontogenetic and static allometries in head shape, as well as sexual dimorphism after size correction. Regarding sexual dimorphism, females tend to have larger heads, besides slightly anteriorly positioned nostrils, smaller eyes, larger canthal ridges, narrower and longer frontoparietal ridges, and larger and laterally shifted squamosal ridges. We discuss the relevance of head morphology variation in the species, as well as the presumed consequences on the species fitness.